2019
DOI: 10.1021/acs.inorgchem.8b02610
|View full text |Cite
|
Sign up to set email alerts
|

Selenidostannates and a Silver Selenidostannate Synthesized in Deep Eutectic Solvents: Crystal Structures and Thermochromic Study

Abstract: Deep eutectic solvents (DESs) have been adopted as reaction media for solvothermal synthesis of crystal materials. In the present work, we extended the scope of DESs in chalcogenidometalate preparation by including dimethylamine, ethylamine, and trimethylamine hydrochlorides and synthesized a series of novel Sn-Se and Ag-Sn-Se compounds: i.e., [NH2(CH3)2]2Sn3Se7·0.5NH­(CH3)2 (1), [NH4]2Sn4Se9 (2), [NH3C2H5]2Sn3Se7 (3), and [NH4]3AgSn3Se8 (4). Compounds 1 and 3 possess honeycomb lamellar [Sn3Se7] n 2n– structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 82 publications
0
32
0
Order By: Relevance
“…[ 51,52 ] Besides, the hydrolysis of urea during the reaction offers ammonium cations as both templating and charge‐balancing agents to construct the anionic ribbon‐stacking lattice of SbS‐1 with appropriate channels responsible for the ion transfer and fixation. [ 53,54 ] Two parameters need to be finely tuned for synthetic optimization. 1) The synthesis for SbS‐1 requires a temperature above 180 °C, as lower temperatures lead to obviously reduced yield (Figures S2 and S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 51,52 ] Besides, the hydrolysis of urea during the reaction offers ammonium cations as both templating and charge‐balancing agents to construct the anionic ribbon‐stacking lattice of SbS‐1 with appropriate channels responsible for the ion transfer and fixation. [ 53,54 ] Two parameters need to be finely tuned for synthetic optimization. 1) The synthesis for SbS‐1 requires a temperature above 180 °C, as lower temperatures lead to obviously reduced yield (Figures S2 and S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…272 273 Various nanoporous (silver) selenidostannates were prepared by Wang et al from eutectic mixtures of alkylamine hydrochlorides, with interesting tuneable properties such as reversible thermochromism. 274 It has been shown that the choice of DES strongly dictates the growth process. 275 Even sheet and flower-like nanostructured hierarchical intermetallic nitro-sulfide compounds have been synthesised: Here, mixed-metallic DESs containing FeCl 3 .6H 2 O, CoCl 2 .6H 2 O and NiCl 2 .6H 2 O were directly annealed at 350 °C for 12 hours.…”
Section: Bottom-up Wet-chemical Synthesis Of Nanoparticles Employing Desmentioning
confidence: 99%
“…27,28 This contributes to a more efficient and faster synthesis for selenidostannate within hours compared to those conducted in neutral, volatile organic solvents (e.g., ethanol and dimethylformamide, DMF). 29,30 Besides, the choline component of DES acts as significant templates and counter cations that account for the construction of honeycomb-like [Sn 3 Se 7 ] n 2n− layers, whose parallel stacking gives the final hybrid of Ch-Sn 3 Se 7 (Figure 2). In the crystal lattice, all of the choline templates exhibit the same activation energy for release/decomposition in response to external thermal stimuli, implying that they can be precisely removed upon heating to a certain temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%